2017
DOI: 10.30813/bmj.v13i2.917
|View full text |Cite
|
Sign up to set email alerts
|

Menuju Sustainability Dengan Tri Hita Karana (Sebuah Studi Interpretif Pada Masyarakat Bali)

Abstract: <p>This article aims to provide an understanding of the meaning of the local wisdom of Tri Hita Karana (THK) of Bali as a concept to achieve sustainability. THK relevant issues was appointed amid the deterioration of the quality of life of mankind as a result of excessive exploitation of nature. That downturn has also hit Indonesia due to the hegemony of positivist paradigm and tendencies attributing a materialistic rationality. Indeed in THK there are values that ought to be executed to achieve sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
0
10
0
3
Order By: Relevance
“…Here, collectivism within Balinese culture is indicated by "Pawongan". This is following the meaning of Pawongan itself which reflects the belief in Balinese society that life happiness can be achieved through good relations with humans as shown by mutual respect, mutual respect for others, and mutual help and support (Hutasoit and Wau, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Here, collectivism within Balinese culture is indicated by "Pawongan". This is following the meaning of Pawongan itself which reflects the belief in Balinese society that life happiness can be achieved through good relations with humans as shown by mutual respect, mutual respect for others, and mutual help and support (Hutasoit and Wau, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Based on the statement of the informant above, it can be concluded that green accounting and tri hita karana have a very close relationship (Hutasoit and Wau, 2017) in carrying out the operations or management of the company (Di Salvo et al, 2017), especially the hospitality industry in Bali. That explanation also implies that the concept that green accounting is very much in line with government programs (Nezakati et al, 2015) and does not conflict with the local wisdom of tri hita karana (Hutasoit and Wau, 2017), so that it can be stated that the concept of green accounting is a concept that is ideal for environmental preservation (Hasan et al, 2019). One tourism observer who is also a community leader in Denpasar stated that: "Hotels in Bali and also other types of businesses have stated their commitment to support government programs not to use disposable plastic in their business operations.…”
Section: Green Accounting Is An Ideal Concept For Environmental Conservationmentioning
confidence: 99%
“…Preservation of the environment is our focus together with the government, the community, business people and investors. The point is green accounting needs to be applied (Rahman and Reynolds, 2016) to support government programs in preserving the environment (Allam, 2019) based on the tri hita karana philosophy (Hutasoit and Wau, 2017).…”
Section: Green Accounting Is An Ideal Concept For Environmental Conservationmentioning
confidence: 99%
“…Dinamika awig-awig dalam rangka penyesuaian dengan kepentingan masyarakat adat tentunya berpengaruh terhadap keberlanjutan tanah adat di desa adat Tenganan Pegringsingan. Keberlanjutan pada masyarakat Bali secara spesifik dapat dilihat dari tiga dimensi konsep kearifan lokal yang terkandung dalam konsep Tri Hita Karana (Hutasoit 2017). Tri Hita karana terdiri atas tiga dimensi yaitu Parahyangan (hubungan manusia dengan Tuhan), Pawongan (hubungan manusia dengan manusia), dan Palemahan (hubungan manusia dengan alam).…”
Section: Pendahuluanunclassified